Murine germ cell-specific disruption of Ift172 causes defects in spermiogenesis and male fertility. Issue 4 (April 2020) - Zhang, Shiyang; Liu, Yunhao; Huang, Qian; Yuan, Shuo; Liu, Hong; Shi, Lin; Yap, Yi Tian; Li, Wei; Zhen, Jingkai; Zhang, Ling; Hess, Rex A; Zhang, Zhibing
Abstract : Intraflagellar transport (IFT) is a conserved mechanism essential for the assembly and maintenance of most eukaryotic cilia and flagella. IFT172 is a component of the IFT complex. Global disruption of mouse Ift172 gene caused typical phenotypes of ciliopathy. Mouse Ift172 gene appears to translate two major proteins; the full-length protein is highly expressed in the tissues enriched in cilia and the smaller 130 kDa one is only abundant in the testis. In male germ cells, IFT172 is highly expressed in the manchette of elongating spermatids. A germ cell-specific Ift172 mutant mice were generated, and the mutant mice did not show gross abnormalities. There was no difference in testis/body weight between the control and mutant mice, but more than half of the adult homozygous mutant males were infertile and associated with abnormally developed germ cells in the spermiogenesis phase. The cauda epididymides in mutant mice contained less developed sperm that showed significantly reduced motility, and these sperm had multiple defects in ultrastructure and bent tails. In the mutant mice, testicular expression levels of some IFT components, including IFT20, IFT27, IFT74, IFT81 and IFT140, and a central apparatus protein SPAG16L were not changed. However, expression levels of ODF2, a component of the outer dense fiber, and AKAP4, a component of fibrous sheath, and two IFT components IFT25 and IFT57 were dramatically reduced. Our findings demonstrate that IFT172 is essential for normal male fertility and spermiogenesis in mice, probably by modulating specific IFT proteins and transporting/assembling unique accessory structural proteins into spermatozoa.